The Role of Social Media Influencers in Achieving Sustainable Consumption: A Study on Purchase Intention of Recycled Bottled Drinking Water - Ningsih, Intan Yuniarti; Ekasari, Ayu (International Journal of Management Science and Information Technology, 2026)
Indonesia is currently facing serious challenges in managing plastic waste, particularly from single-use packaging such as bottled drinking water. This issue highlights the need for a shift toward more responsible and sustainable consumption behavior. Several companies have introduced innovations in recycled packaging; however, consumers often remain skeptical of environmental claims. In the digital marketing era, social media influencers play a crucial role in promoting eco-friendly products by enhancing brand awareness, brand image, and perceived value, which ultimately influence purchase intention. Despite this potential, previous studies have reported inconsistent findings on the effectiveness of influencers in encouraging green purchase behavior. This study aims to develop a conceptual model to analyze the effect of social media influencers on purchase intention toward recycled bottled drinking water, incorporating mediating variables (brand awareness, brand image, perceived value) and a moderating variable (green skepticism). This research adopts a quantitative approach using a survey method with 290 respondents as the sample. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that Social Media Influencer Endorsement positively influences Purchase Intention directly and indirectly through Brand Image and Perceived Value. Meanwhile, Green Skepticism also moderates the influence of Social Media Influencer Endorsement on Purchase Intention, Brand Awareness, Brand Image, and Perceived Value. However, Brand Awareness does not mediate the influence of Social Media Influencer Endorsement on Purchase Intention. The findings are expected to provide insights for companies in designing effective marketing strategies using social media influencers to promote sustainable consumption.